International Consensus Diagnostic Criteria for Autoimmune Pancreatitis and Its Japanese Amendment Have Improved Diagnostic Ability over Existing Criteria - Masahiro Maruyama; Takayuki Watanabe; Keita Kanai; Takaya Oguchi; Takashi Muraki; Hideaki Hamano; Norikazu Arakura; Shigeyuki Kawa (Gastroenterology Research and Practice)
Objectives. The recent International Consensus Diagnostic Criteria (ICDC) for autoimmune pancreatitis (AIP) and its Japanese amendment developed by the Japanese Pancreas Society (JPS 2011) may have overcome the drawbacks of earlier criteria and achieved a higher diagnostic ability for AIP. The aim of the present study is to evaluate this possibility and identify the underlying causes of this change. Methods. We compared the diagnostic abilities of the ICDC and JPS 2011 with those of the Japanese diagnostic criteria 2006 (JPS 2006), Korean diagnostic criteria (Korean), Asian diagnostic criteria (Asian), and HISORt diagnostic criteria in 110 patients with AIP and 31 patients with malignant pancreatic cancer. Results. The ICDC achieved the highest diagnostic ability in terms of accuracy (95.0%), followed by JPS 2011 (92.9%), Korean (92.2%), HISORt (88.7%), Asian (87.2%), and JPS 2006 (85.1%). Nearly all criteria systems exhibited a high specificity of 100%, indicating that the enhanced diagnostic ability of the ICDC and JPS 2011 likely stemmed from increased sensitivity brought about by inclusion of diagnostic items requiring no endoscopic retrograde pancreatography. The diagnostic ability of JPS 2011 was nearly equivalent to that of the ICDC. Conclusions. The ICDC and JPS 2011 have improved diagnostic ability as compared with earlier criteria sets because of an increase in sensitivity.